FACTORS AFFECTING FIRM VALUE WITH DIVIDEND POLICY AS MODERATING VARIABLE IN CONSUMER NON-CYCLICALS SECTOR INDUSTRIES ON IDX 2020-2022 PERIOD - Hengky, Reynaldi; Sufiyati , Sufiyati (International Journal of Application on Economics and Business, 2024)
This study aimed to examine the factors that effecting firm value with dividend policy as moderating variable. With the use of Return on Assets (ROA) as the proxy of Profitability, Current Ratio (CR) as the proxy of Liquidity, Ln (Total Assets) as the proxy of Firm Size, Debt to Equity Ratio (DER) as the proxy of Capital Structure, Working Capital Turnover Ratio (WCT) as the proxy of Working Capital Turnover for the independent variables. The population in this study utilized secondary data obtained from Indonesia Stock Exchange (IDX) with the sample of Consumer Non-Cyclicals sector industries in the period 2020 – 2022. Resulting 20 companies being selected as the research samples that met the criteria with the use of purposive sampling technique. The data were analyzed using Multiple Linear Regression using SPSS 26. The study results indicated that profitability has a significant effect on firm value, while liquidity, firm size, capital structure, and working capital turnover have no significant effect on firm value. Dividend policy is able to moderate the effect of profitability on firm value, but unable to moderate the effect of liquidity and capital structure on firm value.